Form of Supervision and Guidance of Notaries By The Regional Supervisory Council (Mpd) Regarding Notaries Who Do Not Perform Their Offices - Setiyowati, Elis; Ma'ruf, Umar (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
This study aims to determine and analyze the form of supervision and guidance of notaries by the regional supervisory board (MPD) towards notaries who carry out their duties to prevent violations of the authority of the notary's office and to determine and analyze the sanctions given by the regional supervisory board (MPD) to notaries who do not carry out their duties properly. The approach method in this study is the normative legal approach method. The research specification used is descriptive analytical research. The type of data uses secondary data. Data collection with the library study method. The data analysis method used is qualitative descriptive analysis. The results of the research and discussion in this study are: The form related to the supervision and guidance carried out by the Regional Supervisory Board (MPD) towards notaries is very important in preventing violations of the authority of the office and increasing the professionalism of Notaries. The purpose of supervision is to maintain the integrity of the notary profession, protect public interests, and ensure compliance with applicable laws, so that the notary profession remains trusted as an institution that plays a role in maintaining legal certainty in society. Finally, the implementation of supervision and guidance of notaries by the Sukabumi regional supervisory board (MPD) has been quite good and optimal with the condition of the MPD, namely that good cooperation is needed between the Sukabumi MPD and Notaries in Sukabumi. Implementation of Notary Supervision and Guidance Sanctions by the Regional Supervisory Council (MPD) through supervision (repressive) and guidance (preventive). Furthermore, if there is a Notary who violates Article 7 paragraph (1) letter a UUJN and is proven, a written warning will be given a maximum of 3 times. However, if the Notary who has been warned still has not improved his performance in accordance with the advice of the Regional Supervisory Council (MPD), this violation case can be continued to the Regional Supervisory Council (MPW) level to be given heavier sanctions. Finally, guidance actions (preventive) to prevent the recurrence of violations. Guidance actions taken can be in the form of socialization activities or counseling related regulations that are routinely scheduled for Notaries.